O new physics, where art thou?: a global search in the top sector - Brivio, Ilaria; Bruggisser, Sebastian; Maltoni, Fabio; Moutafis, Rhea; Plehn, Tilman; Vryonidou, Eleni; Westhoff, Susanne; Zhang, Cen (Journal of high energy physics, 2020)
We provide a comprehensive global analysis of Run II top measurements at the LHC in terms of dimension-6 operators. A distinctive feature of the top sector as compared to the Higgs-electroweak sector is the large number of four-quark operators. We discuss in detail how they can be tested and how quadratic terms lead to a stable limit on each individual Wilson coefficient. Predictions for all observables are computed at NLO in QCD. Our SFitter analysis framework features a detailed error treatment, including correlations between uncertainties.